Pengembangan Model BIMA (Budaya, Inkuiri, Mencipta, Aktif) dalam Pembelajaran Menulis Narasi - Nita Anjung Munggaran; Yeti Mulyati; Vismaia S. Damayanti; Dadang S. Anshori (Balai Bahasa Provinsi Bali, 2025)
This study aims to analyze the needs and test the effectiveness of the BIMA (Culture, Inquiry, Creation, and Activity) model in strengthening cultural literacy and improving students' narrative writing skills in higher education. The method used was Research and Development (R&D) with four stages: exploration, prototype design, field trials, and final validation and model revision. Data were obtained through focus group discussions, questionnaires, observations, interviews, and document analysis. Instrument validity was tested through expert and student validation, and qualitative data validity was strengthened through source triangulation and informant review. Quantitative data were analyzed descriptively, while qualitative data were analyzed using the Miles and Huberman interactive model. The results showed that the BIMA model significantly improved students' narrative writing skills by strengthening cultural literacy. The average assessment from the three student groups was categorized as